Intestinal Lipid Metabolism Genes Regulated by miRNAs - Ruiz-Roso, María Belén; Gil-Zamorano, Judit; López de las Hazas, María Carmen; Tomé-Carneiro, Joao; Crespo, María Carmen; Latasa, María Jesús; Briand, Olivier; Sánchez-López, Daniel; Ortiz, Ana I.; Visioli, Francesco; Martínez, J. Alfredo; Dávalos, Alberto (Frontiers in Genetics, 2020)
MicroRNAs (miRNAs) crucial roles in translation repression and post-transcriptional adjustments contribute to regulate intestinal lipid metabolism. Even though their actions in different metabolic tissues have been elucidated, their intestinal activity is yet unclear. We aimed to investigate intestinal miRNA-regulated lipid metabolism-related genes, by creating an intestinal-specific Dicer1 knockout (Int-Dicer1 KO) mouse model, with a depletion of microRNAs in enterocytes. The levels of 83 cholesterol and lipoprotein metabolism-related genes were assessed in the intestinal mucosa of Int-Dicer1 KO and Wild Type C57BL/6 (WT) littermates mice at baseline and two hours after an oral lipid challenge. Among the 18 genes selected for further validation, Hmgcs2, Acat1 and Olr1 were found to be strong candidates to be modulated by miRNAs in enterocytes and intestinal organoids. Moreover, we report that intestinal miRNAs contribute to the regulation of intestinal epithelial differentiation. Twenty-nine common miRNAs found in the intestines were analysed for their potential to target any of the three candidate genes found and validated by miRNA-transfection assays in Caco-2 cells. MiR-31-5p, miR-99b-5p, miR-200a-5p, miR-200b-5p and miR-425-5p are major regulators of these lipid metabolism-related genes. Our data provide new evidence on the potential of intestinal miRNAs as therapeutic targets in lipid metabolism-associated pathologies.